2016
DOI: 10.1016/j.ijpharm.2016.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of polo-like kinase 2 loaded nanoparticles-A novel strategy for (serine-129) phosphorylation of alpha-synuclein

Abstract: Polo like kinase 2 (PLK2), a serine/threonine serum inducible kinase, has been proposed to be the major factor responsible for phosphorylating alpha-synuclein (α-syn) at Serine-129 (Ser-129) in Parkinson's disease (PD). A suitable strategy to gain insights into PLK2's biological effects might be to increase PLK2 intracellular levels with the aim of reproducing the slow progressive neuronal changes that occur in PD. The goal of this study was to develop and characterize a novel drug delivery system (DDS) for PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Concentrations of 50, 100 and 200 µg mL −1 of Tl -SN showed a statistically similar cell proliferation relative to cells growing in DMEM expansion medium (control) and comparable values to those exposed to same concentrations of Bm -SFN, previously reported as good candidates for drug delivery or functionalization by diverse compounds with anti-inflammatory, anti-oxidant or anti-tumour properties, among others 29 , 32 , 34 , 43 , 44 . These Tl -SN results, together with those obtained from Tl- S films indicate a good cytocompatibility and no-cytotoxicity of the Tl -S.…”
Section: Resultssupporting
confidence: 56%
“…Concentrations of 50, 100 and 200 µg mL −1 of Tl -SN showed a statistically similar cell proliferation relative to cells growing in DMEM expansion medium (control) and comparable values to those exposed to same concentrations of Bm -SFN, previously reported as good candidates for drug delivery or functionalization by diverse compounds with anti-inflammatory, anti-oxidant or anti-tumour properties, among others 29 , 32 , 34 , 43 , 44 . These Tl -SN results, together with those obtained from Tl- S films indicate a good cytocompatibility and no-cytotoxicity of the Tl -S.…”
Section: Resultssupporting
confidence: 56%
“…TEM-based average size was only slightly greater (390 ± 88 nm) than that measured by the DLS method. It is worth emphasizing the similarity of these NPs with other PLGA NPs prepared according to other conventional elaboration methods [26][27][28].…”
Section: Discussionmentioning
confidence: 84%
“…The NPs Zeta potential was negative either with (-−16.9 ± 0.1 mV) or without (-−16.7 ± 0.2 mV) encapsulated enzyme, and its values agree with those reported in other studies for PLGA NPs (Panyam et aland Labhasetwar 20023). For instance, Rodriguez-Nogales et al [26] reported a practically coincident Zeta potential for PLGA NPs (-−16 ± 2 mV), which was ascribed to the acid functional groups of the copolymer in NPs polymer matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Given the colocalization of α-syn with the lysosomal marker cathepsin D, the immunized mice could activate degradation pathways and thus eliminate α-syn more efficiently [203]. Following this study, another vaccination approach fused α-syn epitopes (α-syn [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] , α-syn [109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] , α-syn [126][127][128][129][130][131][132][133][134][135][136][137][138][139]…”
Section: Active Immunizationmentioning
confidence: 99%
“…The modulation of PLK2-mediated phosphorylation was obtained by its inhibition with selective and brain-permeable chemical compound BI2536 [121,122]. In WT mice and rats, treatment with BI2536 inhibited pS129 α-syn [121,124], and could be delivered locally by nanoparticles [125] but the exact consequences on this inhibition on the pathology of PD are still to be decrypted. However, as kinases phosphorylating α-syn have ubiquitous distribution and possibly compensatory effects, the development of safe and efficient brain-penetrant compounds selectively modulating this PTM is extremely challenging.…”
Section: Phosphorylationmentioning
confidence: 99%